Determinants of perineal wound healing in 2023 - Sukamti, Sri; Noviani , Vicky Agista (Journal of Health Technology Assessment in Midwifery, 2024)
Normal labour can result in a perineal laceration due to pressure from the baby's bottom during delivery or from an episiotomy operation to open the birth canal. Perineal injuries will have an impact on the muscles in the pelvic floor. In the East Jakarta region, there will be numerous cases of perineal rupture in 2022, both spontaneous and due to episiotomy. Many postpartum women suffer from perineal lacerations that take longer than seven days to heal. This study aims to identify the factors that influence perineal wound healing in the Kramat Jati District Health Center's operational setting. This study used a cross-sectional design. Based on the sample formula, the research sample of 110 postpartum women with perineal wounds was chosen to test the hypothesis with a different percentage. Purposive sampling was used as the sample method. Chi-Square test study of a correlation test. A questionnaire and a checklist were employed as the data collection tools to track the healing of the perineum wound, which was assessed during the respondent's postpartum visit. The results showed that there was a significant association between age (P-value 0.003; OR 3.354), parity (P-value 0.001; OR 4.028), mobilization (P-value 0.007), personal hygiene (P-value 0.001; OR 3.611), body mass index (BMI) (P-value 0.012; OR 2.682), type of perineal injury (P-value 0.001; OR 0.251), treatment (P-value 0.0001; OR 5.262) on perineal wound healing. Postpartum mothers are advised to practice good hygiene, non-pharmacological therapies, engage in active mobilization, and maintain a normal BMI. Perineal wounds might heal more quickly depending on BMI. Health services require education for health workers and perineal wound care recommendations for postpartum women.